Current Management of Congenital Pulmonary Airway Malformations: A “European Pediatric Surgeons' Association” Survey - Morini, Francesco; Zani, Augusto; Conforti, Andrea; van Heurn, Ernest; Eaton, Simon; Puri, Prem; Rintala, Risto; Lukac, Marija; Kuebler, Joachim F.; Friedmacher, Florian; Wijnen, Rene; Tovar, Juan Antonio; Pierro, Agostino; Bagolan, Pietro; on behalf of the EUPSA Network Office (European Journal of Pediatric Surgery, 2018)
Aim To define current management of congenital pulmonary airway malformation (CPAM).Methods A total of 181 European Pediatric Surgeons' Association members (91% senior) from 48 countries completed an online questionnaire.Main Results Prenatal: 93% respondents work in centers with prenatal diagnosis facilities, and 27% in centers offering in utero surgery. Prenatal counseling is performed by 86% respondents, 22% of whom see >10 cases per year. Risk of single pre-/postnatal complications is deemed low (<5%) by more than 60% of respondents. Eighty-six percent respondents do not offer pregnancy termination for prenatally diagnosed CPAM. Fetal hydrops is the most frequent indication for termination (87%), followed by parental willingness (52%). Prenatal surgery is an option for 44% respondents, preferring thoracoamniotic shunt (82%).Postnatal: 75% respondents operate on asymptomatic patients, 18% before 6 months of age, 62% between 6 and 12 months of age, and 20% after 12 months of age. Risk of infection (86%), cancer (63%), and symptoms development (62%) are indications for surgery in asymptomatic CPAM. Sixty-three percent prefer a thoracotomy. Lobectomy is the preferred procedure (58% respondents). Motivations against surgery include lesion <1 cm (64%), risk of postoperative complications (37%), and lack of evidence favoring surgery (27%). Seventeen percent respondents have seen at least one patient with CPAM with lung cancer, in 89% of the cases within the CPAM. Of all the respondents, 83% and 22% offered dedicated follow-up and genetic screening, respectively.Conclusion Current pre- and postnatal management of CPAM lacks uniformity, particularly for surgical indication, timing, and approach. Efforts should be made toward standardization. Risk of CPAM-associated cancer is not clear.
Keywords: congenital lung anomalies; observation; postnatal; prenatal; surgery